How Cameroonian Cultural Heritage is Rich but Neglected: A Critical Analysis of the Roles and Responsibilities of Various Stakeholders - Flaure, . Mipo Tchinkou Edith; Hafis, Mohamadou (MAJ - Malaysia Architectural Journal, 2025)
Heritage is what a country inherits from its past, both in material and immaterial forms, such as artistic creations, ancient civilizations, monuments, and natural reserves. In architecture, heritage shows the human achievements that mark a period, a culture, or an event, and help pass on history and identity to future generations. It is an important way of expressing the history and identity of a people. Cameroon has a rich and diverse heritage, including archaeological (the Shum Laka site that is over 30,000 years old), architectural, intangible, and cultural landscapes that are spread across different regions. Two of these sites are recognized as World Heritage by UNESCO: the Dja Faunal Reserve (DFR) and the Sangha Trinational. To preserve this valuable legacy, it is essential to start with a thorough identification of the Cameroonian heritage catalog. This study should evaluate the current condition of each site, monument, artistic and architectural work, and define appropriate measures to increase their visibility and value. This involves finding accurate methods for conservation, restoration, and maintenance that ensure proper valorization and transmission to future generations. Then, it will be important to think of ways to raise awareness and appreciation of Cameroonian heritage among communities and populations to encourage better valorization. The goal of valorizing this heritage is to make the historical narrative available and thus promote Cameroonian culture, both locally and globally.